PSYCHOLOGICAL STRESS AND ITS ROLE IN THE COURSE OF PSORIASIS: A REVIEW OF THE LITERATURE - Aleksandra Gęsińska,; Patryk Kowalczyk,; Oliwia Gugała,; Igor Winogrodzki,; Alicja Stryczek-Schlusche,; Aleksandra Magdalena Furczyńska,; Bartłomiej Trzciński,; Hanna Paszkiewicz,; Kamil Nowak,; Filip Bracichowicz, (International Journal of Innovative Technologies in Social Science, 2025)
Psoriasis is a chronic inflammatory skin disease whose course is significantly modulated by psychosocial factors, especially stress. Increasing evidence suggests that stress can both initiate the first symptoms and exacerbate disease activity and promote recurrence. The mechanisms underlying this phenomenon include activation of the hypothalamic-pituitary-adrenal axis, dysregulation of the neuroimmunological response, and increased expression of proinflammatory cytokines, which maintain chronic skin inflammation. The aim of this review was to summarize the current knowledge on the relationship between stress and psoriasis and to evaluate the effectiveness of psychological interventions and stress reduction techniques as adjuncts to standard dermatological treatment.A review of the literature shows that interventions such as cognitive behavioral therapy (CBT), mindfulness programs (MBSR/MBCT), relaxation training, and biofeedback consistently improve mental well-being (including reducing anxiety and depression) and quality of life. Some studies have also reported a beneficial effect on the severity of skin changes. Furthermore, attention has been drawn to the importance of coping styles and social support, which can modify the response to stress and the course of the disease.The limitations of the available studies include small sample sizes, heterogeneity of protocols, and short follow-up periods, which make it difficult to compare results and assess the durability of effects. In the future, well-designed randomized trials with longer follow-up periods are needed, as well as research on neurological and immunological biomarkers that will facilitate objective assessment of efficacy. The integration of psychological components into the biopsychosocial model seems to be a reasonable direction for optimizing the care of patients with psoriasis.